Why free does not mean fair: Investigating users' distributive equity perceptions of data-driven services. (August 2021) - Wagner, Amina; Wessels, Nora; Brakemeier, Hendrik; Buxmann, Peter
Highlights: Validation of a new distributive equity scale for free data-driven services. Reconceptualization of individual's perception of these services. User's and provider's net value is related to distributive equity perceptions. The higher distributive equity perceptions the higher user's satisfaction. Satisfaction mediates the link between distributive equity and continued use. Abstract: Individuals are supposed to perform a privacy risk-benefit analysis when deciding to transact with a free data-driven service provider. Building on equity theory, this article suggests that users incorporate the net value for providers in their trade-off. Based on two pre-studies and an experimental survey study among 200 free data-driven service users, we provide evidence that users' balance their own net value (benefits minus risks) as well as providers' net value from monetizing users' data. This leads to distributive equity perceptions which, in turn, affect users' satisfaction with the service and thus long-term success of the user-provider-relationship. In this vein, a distributive equity scale for the context of data-driven services is developed. Implications for research, providers and users are discussed.